Nigerian Ports Authority (Lagos, Nigeria : Nigeria Ports Authority, 1969)
This report covers the contribution of the Nigerian Ports Authority to the Nigerian economy between 1968-69.
Fourteenth annual report for the year ended 31st March, 1969.
ne 16/04/2019
Ref
Keywords: Port facilities; Port facilities--Transportation services; Nigeria